2020
DOI: 10.3389/fnins.2020.575521
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Synchrony in EEG, Electrodermal Activity and Heart Rate Detects Attentionally Relevant Events in Time

Abstract: Interpersonal physiological synchrony (PS), or the similarity of physiological signals between individuals over time, may be used to detect attentionally engaging moments in time. We here investigated whether PS in the electroencephalogram (EEG), electrodermal activity (EDA), heart rate and a multimodal metric signals the occurrence of attentionally relevant events in time in two groups of participants. Both groups were presented with the same auditory stimulus, but were instructed to attend either to the narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
(70 reference statements)
0
29
0
Order By: Relevance
“…The first experiment has been conducted and the first papers, number one and two in Table 1, have been published [? ] and submitted [35], respectively. In paper one, we monitored EEG, EDA and heart rate across 26 participants that were either instructed to focus their attention on a 66 minute audiobook (𝑁 = 13) or on interspersed emotional sounds and beeps they had to keep track of (𝑁 = 13).…”
Section: Initial Resultsmentioning
confidence: 99%
“…The first experiment has been conducted and the first papers, number one and two in Table 1, have been published [? ] and submitted [35], respectively. In paper one, we monitored EEG, EDA and heart rate across 26 participants that were either instructed to focus their attention on a 66 minute audiobook (𝑁 = 13) or on interspersed emotional sounds and beeps they had to keep track of (𝑁 = 13).…”
Section: Initial Resultsmentioning
confidence: 99%
“…We compare the performance of NSTE asymmetry to a more traditional measure of physiological synchrony: the single session index. Introduced by Marci and Orr ( 2006 ) with several more recent modifications (Slovák et al, 2014 ; Karvonen et al, 2016 ; Haataja et al, 2018 ; Malmberg et al, 2019 ; Misal et al, 2020 ; Stuldreher et al, 2020 ), the SSI has been well-established with electrodermal activity signals. Previous work has demonstrated that high SSI measured from EDA signals between individuals have been associated with high levels of dyadic and group emotional engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals have different dominant physiological modalities and may manifest synchrony in other biosignals (e.g., heart rate) (Lai Kwan et al, 2019). Other studies have shown that performance of a multimodal physiological synchrony measure was more robust than a single physiological metric across different types of stimuli, even though the maximum performance did not improve over a single physiological metric (Verma and Tiwary, 2014;Stuldreher et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While physiological synchrony in EEG has been demonstrated in the classroom ( Dikker et al, 2017 ), easier, less obtrusive collection and processing of data would make interpersonal physiological synchrony a more suitable measure for attention in the classroom. Therefore, within the NeurolabNL Startimpulse project, we determined whether other physiological measures, namely heart rate and skin conductance, provide similar insights into attentional allocation as EEG ( Stuldreher et al, 2020a , b ). In this study, participants listened to the same audiobook, mixed with other sounds.…”
Section: The Neurolabnl Startimpulse Project: Optimal Conditions For Education and Social Safety Of Youthmentioning
confidence: 99%